Sistem Pendukung Keputusan untuk Pemilihan Jasa Pengiriman Terbaik pada Bisnis Online Menggunakan Metode SMART dan ROC - Widodo, Tri (PT. Tech Cart Press, 2024)
Delivery services are services that provide logistics solutions to deliver goods or documents from one location to another efficiently and on time. The main problem in choosing the best delivery service lies in the complexity of assessing various criteria that affect the quality of service. In addition, the information available from service providers is often subjective and does not reflect actual performance, hindering objective decision-making. The choice of delivery service can also be affected by the lack of accurate information about the service's performance, especially if customers only rely on reviews or recommendations that do not necessarily reflect the true quality. In addition, the selection based on the cheapest price without considering the quality aspect can risk the safety and timeliness of delivery of goods. As a result of calculating the utility value using the SMART method, the best delivery service alternative for online businesses is Jasa C, which obtained the highest utility value of 0.9100, making it the first choice in the ranking. In second place, there is Jasa E with a utility value of 0.5548, which shows a fairly good performance although not as high as Jasa C. Jasa A follows in third place with a utility value of 0.4778, which indicates that this alternative has a lower performance than the top two delivery services. The results of this ranking provide a clear picture of the performance of each delivery service, which can be used as a basis for decision-making to choose the optimal delivery service according to the needs of online business.